Constitutional Court Regression in Post- Democratic Transition: A Comparison of Court Packing in Hungary, Poland, and Indonesia - Idul Rishan (Constitutional Review, 2024)
Over the past two decades, the constitutional court established in the post-democratic transition has begun to face regression. The Constitutional Courts in Hungary, Poland, and Indonesia have evidence, carried out intensively through court packing. This article investigates the regime’s undermining of the constitutional court against constitutional judges in selected countries. In addition, this article will also describe the regime’s motives and objectives in undermining the independence of the constitutional court. This study argues that regression of the constitutional court occurs through several patterns, such as increasing and decreasing the number of constitutional judges, politicizing the appointment and dismissal of constitutional judges, and rearranging the requirements and selection procedures of constitutional judges. The regime uses court packing to place judges who are loyal or have the same political preferences as the regime to provide control over their independence.